The pursuit of peace and the character of modern state : a critical revision of Michael Oakeshott’s philosophy of history and its application to the study of international political thought - Gabriel, Fernando da Cruz (2013)
The argument of this thesis intends to show how the philosophy of Michael Oakeshott can be used for the study of intellectual history. In order to do so, I will first approach Oakeshott’s philosophy as an epistemology, and argue that there is a movement detectable in his works, from an earlier metaphysical idealism detectable in the works of the 1920’s, which was substantially modified in Experience and its Modes but retained most of the identity characteristics of the British idealism, towards the final formulation as a form of post-metaphysical, non-foundational contextualism that characterises On Human Conduct, published in the 1970’s. The common thread uniting Oakeshott’s successive philosophical formulations is the search for a viable philosophical “platform of understanding”, capable of safeguarding the autonomy of the theoretical idioms of understanding and of surmounting several important difficulties that have plagued most post-foundational philosophies, namely philosophical scepticism, a search that I will argue reached a successful culmination in On Human Conduct. I will then argue that Oakeshott’s philosophy contains a valuable contribution to the understanding of the practice of historiography, which may be characterised as a form of historicism that simultaneously rejects naturalism and narrativism as unhistorical forms of explanation. However, Oakeshott’s historicism is “uneven”, in the sense that his satisfactory treatment of the questions of historical interpretation contrasts with the relative neglect of the questions of historical representation: as instruments for an historical understanding of the existing and complex human associations, Oakeshott’s ideal characters of civil association, or societas, and enterprise association, or universitas, describing two opposing modes of political association, are overly schematic. This insufficiency will be addressed through the construction of an extended version of the ideal modes of societas and universitas, which will be transformed into a richer base of ideal characters by recourse to the narrative archetypes of Romance, Satire, Comedy and Tragedy, thus creating four “micromodes” of political association. These ideal characters are intended to be particularly suited to capture stylistic differences in written utterances, and are therefore apt to be use in the historical study of political thought; accordingly, their usefulness will be illustrated through their application to the study of a set of writings by Benjamin Constant, Jeremy Bentham, Leonard Woolf and Hans Morgenthau, united by their common theme, which is a moral dimension of world politics: the pursuit of peace and its connection with the character of the activity of government. The study presents a fresh interpretation of Oakeshott’s philosophy and innovates in the use of modality as an “open-ended” structure, illustrating its possibilities for the historical study of political thought.